Effects of relative centrifugation force on L‐PRF: An in vivo submandibular boney defect regeneration study. Issue 12 (3rd June 2021) - Tovar, Nick; Benalcázar Jalkh, Ernesto B.; Ramalho, Ilana S.; Rodriguez Colon, Ricardo; Kim, Heoijin; Bonfante, Estevam A.; Torroni, Andrea; Coelho, Paulo G.; Witek, Lukasz
Abstract: Properties and composition of leukocyte‐ and platelet‐rich fibrin (L‐PRF) clots may be largely affected by centrifugation protocols (function of relative centrifugal force [RCF]), which may impact biological potential repair in bone regeneration. The present in vivo study sought to assess the effect of the RCF on the composition of L‐PRF clots, as well as to compare the repair potential of L‐PRF clots obtained with different RCF protocols in submandibular boney defects using PLGA scaffolds for bone regeneration. Complete blood count and volumetric evaluations were performed on L‐PRF clots obtained through centrifugation for 12 min at 200, 400, and 600 RCF‐clot centrifugation speeds. These evaluations were completed from blood collected immediately prior to any surgical procedures. The in vivo portion comprised of three submandibular unilateral, full thickness, osteotomies (~0.40cm 3 ) which were created in the submandibular region of six sheep, using rotary instrumentation under continuous irrigation. Subsequently, poly(lactic‐co‐glycolic acid) (PLGA) scaffolds were enveloped in a L‐PRF membrane from one of the three spinning speeds (n = 6/RCF) and inserted into the defect (sites were interpolated to avoid site bias). Six‐weeks after surgery, the mandibles were harvested en bloc and prepared for volumetric and histomorphometric evaluations. Membranes harvested from 600 RCF produced significantly larger L‐PRF clots (6.97 g  ± 0.95) in comparison to the lower 200 RCF (5.7 g  ± 0.95), with no significant differences between 600 and 400, and from 400 and 200 RCF. The three tested RCFs did not alter the platelet count of the L‐PRF clot. For the in vivo component, quantitative bone regeneration analyses demonstrated significantly higher values obtained with L‐PRF membranes extracted post 600 RCF (27.01 ± 8%) versus 200 RCF (17.54 ± 8%), with no significant differences regarding 400 RCF (~23 ± 8%). At the qualitative histological analyses, L‐PRF membranes obtained at 600 and 400 RCFs yielded improved healing throughout the defect, where the L‐PRF sourced from the lowest speed, 200 RCF, presented healing primarily at the margins along with the presence of connective tissue at the central aspect of the surgical defect. Higher 600 RCF yielded larger L‐PRF clots/membranes, resulting in enhanced bone repair potential in association with PLGA scaffolds for the treatment of critical size bone defects.